Bullseye - Patterson, James 1947-; Ledwidge, Michael; Mastrogiorgio, Danny (New York, NY : Hachette Audio, 2016)
Tensions between America and Russia are the highest they've been since the Cold War. As the countries' two presidents travel to the United Nations to iron out their differences, a fashionable husband and wife team of lethal special ops assassins prowls the streets of Manhattan hunting their prey, a law school professor hiding a scandalous secret.
Keywords: Bennett, Michael (Fictitious character) -- Fiction; Police -- Fiction -- New York (State); Assassins -- Fiction; Manhattan (New York, N.Y.) -- Fiction; Detective and mystery fiction; Thrillers (Fiction); Audiobooks